Development of a five-tier diagnostic test instrument to identify the level of understanding and misconceptions on the subject of equilibrium of rigid bodies at SMA Negeri 9 Jambi City - Putri Handayani Simatupang; Maison Maison; M. Hidayat (Universitas Ahmad Dahlan, 2023)
This research aims to identify students' misconceptions regarding website-based rigid body equilibrium material at SMA Negeri 9, Jambi City. This research focuses on developing a diagnostic paper-based test (PBT) in the form of a website. This research method is R&D (Research and Development) development with the ADDIE (analysis, design, development, implementation, evaluation) development model. However, this research has only reached the implementation stage. The instruments used in the research were the results of media questionnaires, instrument validation, and student responses. The research results are as follows: First, Dreamweaver, MySQL, and HTML can be used in website development. Second, the results of this product development can be used because they have been validated by media experts, namely Validator One and Validator 2, to determine the feasibility of the product being developed. Thus, a five-tier diagnostic test in the form of a paper-based test has been successfully developed into a website with a suitable category for identifying misconceptions among students regarding the equilibrium of rigid bodies.